Menggereja Bersama Kaum Miskin: Relevansi Ulangan 15: 1-11 - Edward Jakson Turalely; Monike Hukubun (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
Poverty has been at the core of human civilization and a major problem in the nation-building process. Therefore, this article aims to make relevant the theological meaning of Deuteronomy 15:1–11, which has been studied ideologically, to the reality of poverty in Maluku. This effort was carried out using the literature study method by studying and analyzing several references related to the theological meaning of Deuteronomy 15:1–11 and the dialogue with the context of poverty in Maluku. Based on the research process, a theology of the church with the poor in Maluku was produced. All components are called to understand that God is on the side of the poor and then put it into practice in the reality of life, which is increasingly threatened. The theology of churching with the poor as the main thesis of this research is discussed in three analytical frameworks: revealing the reality of poverty in Maluku, interpreting the ideology of Deuteronomy 15:1–11, and finding the perspective of God's partiality towards the poor. , and ending with the praxis of GPM's ecclesiology.